Faktor-Faktor yang Mempengaruhi Kejadian Asfiksia pada Bayi Baru Lahir di RS Aura Syifa Kabupaten Kediri - Sumi Dwi Antono (Akademi Keperawatan Dharma Husada Kediri, 2018)
Asphyxia neonatorum is a spontaneous and regular respiratory failure at birth. Asphyxia is a major cause of stillbirth and neonatal death. It could be caused by several factors, among others the Pre-labor Rupture Of Membrane (PROM), pregnancy over time, fetal weight is not appropriate during pregnancy, breech position, birth less months, neglected labour, and amniotic fluid mixed with meconium. This study aims to determine what risk factors affect the incidence of asphyxia in newborns in RS Aura Syifa Kediri District. The type of this research was an observational analytics with cross sectional design, and used a chi-square and fisher's exact test to determine the relationship. Probability sampling with systematic random sampling method was used as the sampling technique. The populations in this study were all infants who were diagnosed asphyxia in Aura Syifa Hospital of Kediri District. The samples were 61 respondents who meet the inclusion and exclusion criteria. Results obtained from the fisher’s exact test with value (α 5% = 0,05 is 1) P-value factor PROM 0,207; 2), P-value factors of pregnancy over time 0,068; 3), P-value factor Low Birth Weight (LBW) 0,077; 4), P-value factor breech position 0,253. In a nutshell, it can be concluded PROM, pregnancy over time, Low Birth Weight (LBW) and breech location does not have a significant relationship with the incidence of asphyxia in newborns in RS Aura Syifa Kediri District. Keywords: Asphyxia, LBW, pregnancy over time, PROM, breech